Earnings Management Analysis of Basic Materials Firms Listed on the Indonesia Stock Exchange (2021-2023) with Firm Size as a Moderating Variable - Lovelytan, Fidelia; Novia, Novia; Sonia, Sonia (JMK (Jurnal Manajemen dan Kewirausahaan), 2025)
This study was conducted to investigate how Audit Quality, Profitability, Leverage, Information Asymmetry, and Tax Planning influence Earnings Management. It also aims to understand how Firm Size moderates or affects the impact and form of the connection among the variables that are independent and dependent. The methodological framework applied is causal comparative with a quantitative approach. Financial reports of firms within the Basic materials that are listed between 2021 and 2023 on the Indonesia Stock Exchange provided the data for this scrutiny. Employing a purposive sampling technique to select the research sample, resulting in 84 firms which satisfied the research requirements, yielding 252 observations. Multiple linear regression analysis was used to evaluate the first hypothesis, while the absolute difference test methodology was used to examine the second. The findings revealed that Audit Quality, Profitability, and Information Asymmetry did not have a major impact on Earnings Management. However, Leverage and Tax Planning had a negative impact on Earnings Management. The results also indicated that Firm Size significantly moderated the connection between Tax Planning and Earnings Management. However, Firm Size was not proven to moderate the connection among Audit Quality, Profitability, Leverage, and Information Asymmetry with Earnings Management.